Turbulent flow around a square cylinder at Reynolds number 22, 000: A DNS study. (21st December 2015) - Trias, F.X.; Gorobets, A.; Oliva, A.
Highlights: DNS results of the turbulent flow around a square cylinder at R e = 22, 000 are presented. A significantly larger domain has been used compared with previous numerical studies. Around 80 shedding cycles have been computed using 323 million grid-points. Time-averaged flow and turbulent statistics show a good agreement with experiments. Averaged drag value, C d = 2.18, is slightly higher than the experimental results. Abstract: The turbulent flow around a square cylinder at Reynolds number 22, 000 (based on the cylinder diameter and the inflow velocity) is studied by means of direct numerical simulation. An overview of the numerical methods and the methodology used to verify the simulation is presented with special emphasis to determine the proper domain size and time-integration period. Then, the time-averaged flow results and turbulent statistics are discussed together with available experimental data showing a fairly good agreement. Finally, frequency analysis of velocity samples is used to analyze both the Kelvin–Helmholtz vortical structures produced by the flow separation at the leading edge of the cylinder and the Von Kármán vortex shedding in the wake region. The former are observed more downstream compared with the experiments suggesting that transition to turbulence may occur later. However, comparison of the turbulent statistics in the near wall region indicates that transition is being well captured.